Bridging Mathematics, Statistics, Engineering and Technology Contributions from the Fall 2011 Seminar on Mathematical Sciences and Applications - Toni, Bourama.; Toni, Bourama.; Williamson, Keith.; Williamson, Keith.; Ghariban, Nasser.; Ghariban, Nasser.; Haile, Dawit.; Haile, Dawit.; Xie, Zhifu.; Xie, Zhifu. (Springer Proceedings in Mathematics & Statistics, 2012)
This volume contains the invited contributions from talks delivered in the Fall 2011 series of the Seminar on Mathematical Sciences and Applications 2011 at Virginia State University. Contributors to this volume, who are leading researchers in their fields, present their work in a way to generate genuine interdisciplinary interaction. Thus all articles therein are selective, self-contained, and are pedagogically exposed and help to foster student interest in science, technology, engineering and mathematics and to stimulate graduate and undergraduate research and collaboration between researchers in different areas.   This work is suitable for both students and researchers in a variety of interdisciplinary fields namely, mathematics as it applies to engineering, physical-chemistry, nanotechnology, life sciences, computer science, finance, economics, and game theory.